2022
DOI: 10.3390/nu14194120
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Ameliorates Skeletal Muscle Atrophy and Improves Insulin Resistance in High-Fat-Diet-Induced Insulin Resistance in Obese Rats

Abstract: Obesity causes progressive lipid accumulation and insulin resistance within muscle cells and affects skeletal muscle fibres and muscle mass that demonstrates atrophy and dysfunction. This study investigated the effects of naringin on the metabolic processes of skeletal muscle in obese rats. Male Sprague Dawley rats were divided into five groups: the control group with normal diet and the obese groups, which were induced with a high-fat diet (HFD) for the first 4 weeks and then treated with 40 mg/kg of simvasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…[37] Furthermore, Hao et al [38] found patients with concomitant exotropia exhibited statistically smaller medial rectus sizes by using high-resolution MRI. It is hypothesized that obesity-induced muscle atrophy [39][40][41][42][43] may be a contributing factor to the development of concomitant exotropia. At the molecular level, matrix metalloproteinases (MMPs) showed a positive correlation with the severity of intermittent exotropia, while tissue inhibitors of metalloproteinase (TIMPs) showed a negative correlation.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Furthermore, Hao et al [38] found patients with concomitant exotropia exhibited statistically smaller medial rectus sizes by using high-resolution MRI. It is hypothesized that obesity-induced muscle atrophy [39][40][41][42][43] may be a contributing factor to the development of concomitant exotropia. At the molecular level, matrix metalloproteinases (MMPs) showed a positive correlation with the severity of intermittent exotropia, while tissue inhibitors of metalloproteinase (TIMPs) showed a negative correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Naringin, a naturally occurring component in citrus fruits, alleviates insulin resistance and improves skeletal muscle atrophy. Termkwancharoen et al ( 17 ) revealed that in high-fat-diet-induced obese rats, naringin is an alternative supplement that improves the treatment of dyslipidaemia, decreases obesity-induced muscular dysfunction, and reduces insulin resistance while increasing sensitivity. Scutellarein, an active component in Erigeronbrevis-capus (Vant.…”
Section: The Mechanism Of Flavonoids On T2dmmentioning
confidence: 99%
“…Simultaneously, it reduces α-GPDH enzyme activity, MyHC II expression, and the proportion of fast-twitch bers. Additionally, naringin boosts serum adiponectin levels, activating the expression of AdipoR1, APPL1, AMPK, and PGC-1α, thereby facilitating the transition of skeletal muscle bers from fast-twitch to slow-twitch states [35][36][37]. C2C12 cells are commonly used to study muscle development, muscle nutrient metabolism, and other muscle-related biological processes.…”
Section: Introductionmentioning
confidence: 99%